Freestanding hierarchical NiO/MnO2 core/shell nanocomposite arrays for high-performance electrochemical energy storage. (10th February 2017) - Yuan, Y.F.; Lin, J.X.; Zhang, D.; Yin, S.M.; Zhao, Y.L.; Yang, J.L.; Chen, Y.B.; Guo, S.Y.
Abstract: Freestanding hierarchical NiO/MnO2 core/shell nanocomposite arrays were synthesized by a two-step method including chemical bath deposition and hydrothermal reaction. Their morphology and structure were characterized by XRD and SEM. NiO net-like macroporous nanoflake arrays grow on Ni foam as freestanding core backbone material, and MnO2 nanosized mesoporous foams grow on the two sides of NiO nanoflakes, forming secondary shell structure on NiO nanoflakes. Electrochemical performances were examined by cyclic voltammetry (CV), galvanostatic charge-discharge and electrochemical impedance spectroscopy (EIS). NiO/MnO2 nanocomposite arrays show improved electrochemical performance: high specific capacity (190 mAh g −1 at 1 A g −1 and 167 mAh g −1 at 20 A g −1 ) and high cycling stability (92% retention at 2 A g −1 after 4000 cycles) as well as good rate performance. CV testing indicates both NiO and MnO2 participate in the Faradic reactions even though MnO2 nanosized mesoporous foam covers the surface of NiO nanoflakes. EIS shows that charge-transfer resistance and Warburg resistance decrease, which reflects that the nanocomposite structure can improve electrochemical activity of NiO and MnO2 . SEM observation on the cycled electrode confirms the intense synergistic effect of NiO/MnO2 nanocomposite. Electrochemical investigation reveals the freestanding hierarchical NiO/MnO2 core/shell nanocomposite array designed here is a good electrode material for high-performance electrochemical energy storage.